The burden of cervical cancer in China - Shen, Xiu; Cheng, Yiquan; Ren, Fupeng; Shi, Zhilong (Frontiers in Oncology, 2022)
Trends in the incidence, disability-adjusted life-years (DALYs), and mortality rate of cervical cancer remain unknown. The average annual percent changes (AAPCs) and relative risks (RR) in the incidence, DALYs, and mortality rate were determined using a joinpoint regression analysis; the net age, period, and cohort effects on above rates were evaluated. Results: A significant increase in age-standardized incidence (AAPC, 0.9%; 95CI: 0.8, 1.1) but significant decreases in age-standardized DALYs (AAPC, -0.4%; 95CI: -0.60, -0.20) and the mortality rate (AAPC, -0.4%; 95CI: -0.6, –0.3) were observed. As for age-specific rates, the incidence was higher in younger age groups, and the DALYs and mortality rate were lower in older age groups. The effects of age included a slight but significant increase in the RR with advancing age from 35 to 94 years; the period effect included a significant increase in the incidence over the 2005–2020 periods; and the cohort effect included a substantial increase in the incidence from earlier to later birth cohorts. The incidence of cervical cancer increased from 1990 to 2019, particularly in younger age groups, and the DALYs and mortality rate decreased in the older age groups. Furthermore, the incidence increased with age, period, and cohort.